The Association between Degree of Smoking and Myocardial Infarction Prevalence - Derajat Fauzan Nardian; Achmad Arman Subijanto; Yusuf Ari Mashuri (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2016)
Background: Cardiovascular disease is one of the leading causes of death in the world. One of the most common cardiovascular disease is myocardial infarction. In developing countries such as Indonesia, smoking is a risk factor that greatly affects on myocardial infarction disease. Many factors such as the duration of smoking, the number of cigarette consumption and the degree of smoking are thought to be related to the prevalence of myocardial infarction. The aim of this research was to determine the association between degree of smoking and myocardial infarction prevalence. Methods: The study is analytical observation by using cross sectional design. The subjects were patients who came to cardiovascular clinic and inpatients in cardiovascular unit of Dr. Moewardi Hospital Surakarta. The subjects were selected by purposive sampling method. The independent variable is degree of smoking that was obtained by interview and questionnaire and the dependent variable is the myocardial infarction status that was obtained by medical record of the subjects. Data were analyzed using chi-square test with p value = 0.05. Results: The total number of patients with history of myocardial infarction were 22 (50%) whereas patients without history of myocardial infarction were 22 (50%). The number of subjects with light smoking status were 18 (40.9%), moderate smoking status were 15 (34.1%) and heavy smoking status were 11 (25%). Chi-square test on the degree of smoking and the prevalence of myocardial infarction showed that the odds ratio between heavy smoking status and light smoking status was 26 and odds ratio between heavy smoking status and moderate smoking status was 11.43 whereas p value was 0.004 (p < 0.05). Conclusion: It can be concluded that there is difference in myocardial infarction prevalence between heavy, moderate and light smoking status patients in Dr. Moewardi Hospital Surakarta. Keywords: cigarrete, smoking status, degree of smoking, myocardial infarction